A novel experimental study on discharge characteristics of an aluminum‐air battery. (15th February 2019) - Hu, Tianen; Fang, Yidong; Su, Lin; Li, Kang
Summary: In order to explore the discharge characteristics of aluminum‐air battery and find out the best discharge performance of aluminum‐air battery under the optimum working conditions, this paper studies discharge performances of an aluminum‐air battery under various ambient temperature and battery discharge conditions. The relationship between the temperature rise of the battery electrolyte and the discharge current density was studied by an experimental method. Effects of the electrolyte concentration and the ambient temperature on the battery discharge voltage were investigated. In addition, a novel method for calculating the efficiency of the aluminum‐air battery was proposed. Results show that the temperature of the aluminum‐air battery electrolyte gradually increases as its discharge current density increases and the electrolyte temperature rise could reach as high as 10°C after 60 minutes with a constant 35 mA cm −2 discharge current density. The specific energy and the specific capacity of the aluminum‐air battery first increase and then decrease as the current density increases. When the current density is 25 mA cm −2, the specific energy has a peak of 3105 Wh kg −1 for the condition of the chamber temperature 40°C and the electrolyte concentration 2 mol L −1 (2 M), while the specific capacity has a peak of 2207 Ah kg −1 ; furthermore, its efficiencies under various conditions increase first with the current density, reach a peak range of 19.6% to approximately 36% at 25 mA cm −2, and then decrease. These experimental results could be used as a technical guidance for the optimization in thermal management designs of the aluminum‐air battery under various operating conditions. Abstract : Because of the high specific energy, clean, and pollution‐free, the characteristics of aluminum air batteries have received extensive attention. In the article, the relationship between the electrolyte temperature rise and the discharge current density for an aluminum‐air battery is the first available study, and a novel method is proposed to calculate the efficiency of an aluminum‐air battery, at the same time, the effects of ambient temperature on discharge voltage, specific energy, and specific capacity are fully considered.